Chronic hypoventilation syndromes and sleep-related hypoventilation - Böing, Sebastian; Randerath, Winfried J. (Journal of Thoracic Disease; Vol 7, No 8 (August 28, 2015): Journal of Thoracic Disease (Respiratory Sleep Disorders), 2015)
Chronic hypoventilation affects patients with disorders on any level of the respiratory system. The generation of respiratory impulses can be impaired in congenital disorders, such as central congenital alveolar hypoventilation, in alterations of the brain stem or complex diseases like obesity hypoventilation. The translation of the impulses via spinal cord and nerves to the respiratory muscles can be impaired in neurological diseases. Thoraco-skeletal or muscular diseases may inhibit the execution of the impulses. All hypoventilation disorders are characterized by a reduction of the minute ventilation with an increase of daytime hypercapnia. As sleep reduces minute ventilation substantially in healthy persons and much more pronounced in patients with underlying thoraco-pulmonary diseases, hypoventilation manifests firstly during sleep. Therefore, sleep related hypoventilation may be an early stage of chronic hypoventilation disorders. After treatment of any prevailing underlying disease, symptomatic therapy with non-invasive ventilation (NIV) is required. The adaptation of the treatment should be performed under close medical supervision. Pressure support algorithms have become most frequently used. The most recent devices automatically apply pressure support and vary inspiratory and expiratory pressures and breathing frequency in order to stabilize upper airways, normalize ventilation, achieve best synchronicity between patient and device and aim at optimizing patients’ adherence.